A Randomized Trial of Intra-articular Injection Therapy for Knee Osteoarthritis. Issue 5 (27th May 2023) - Tschopp, Marcel; Pfirrmann, Christian W.A.; Fucentese, Sandro F.; Brunner, Florian; Catanzaro, Sabrina; Kühne, Nathalie; Zwyssig, Iwan; Sutter, Reto; Götschi, Tobias; Tanadini, Matteo; Rosskopf, Andrea B.
Abstract : Background: Intra-articular injections are widely used for conservative treatment of knee osteoarthritis (OA). However, rigorous data are lacking regarding the comparative therapeutic effectiveness of these injections. Purpose: The aim of this study was to compare clinical outcomes after intra-articular injections of glucocorticoid, hyaluronic acid, platelet-rich plasma (PRP), or placebo in patients with mild or moderate OA of the knee. Materials and Methods: In a double-blinded, placebo-controlled, single-center trial, we randomly assigned knees with early- to middle-stage knee OA (Kellgren-Lawrence grade 1–3) to an intra-articular injection with one of these substances: glucocorticoid, hyaluronic acid, PRP, or placebo. Primary outcome was pain reduction within 6 months after the injection, assessed with the numeric rating scale (NRS; range, 0–100). Secondary outcome parameters included WOMAC scores, Tegner Activity Scale, knee mobility, and adverse events. Finally, a linear mixed-effects model was calculated and corrected for possible patient and covariate effects. Results: One hundred twenty knees (30 knees per treatment group) in 95 patients (41 female) were included in the final analysis. The median age of patients was 60 years (interquartile range, 54.0–68.0). There was no evidence that the drug effects of primary and secondary outcome parameters differed over time. The median pain at baseline was 32.5 (interquartile range, 15.00–50.00) on NRS. The changes in pain level during the first 6 months compared with baseline were small (within ±5 points on NRS), whereas the intrapatient variability was large between −20 and +20 points. Secondary outcome parameters did not differ significantly among the groups. Kellgren-Lawrence grade did not have a statistically significant effect on pain reduction ( P = 0.61). Conclusions: There is no evidence that knee injections with glucocorticoid, PRP, or hyaluronic acid have superior short- or long-term effects in patients with low pain level at baseline and early- to middle-stage knee OA when compared with placebo.